Calcule: 8 7 2 - 3 6 3 = (2 3) - (0 2) = (1 2 4) - (0 1 2) =
(1 4) (1 5) (6 3 10) (6 5 1)
Anexos:
![](https://pt-static.z-dn.net/files/dd2/53bd4a6deaace246e49976c78def695e.png)
Soluções para a tarefa
Respondido por
1
Resposta:
1= [ 5 ]
[ 1 ]
[ -1 ]
2= [ 2 1 ]
[0 -1 ]
3= a expressão é indefinida
Explicação passo-a-passo:
Não sei se está certo,mas espero ter ajudado
Perguntas interessantes
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Português,
8 meses atrás
Geografia,
8 meses atrás
Química,
1 ano atrás
Matemática,
1 ano atrás